1971
DOI: 10.1139/p71-037
|View full text |Cite
|
Sign up to set email alerts
|

The 4875 Å Band System of cis Glyoxal

Abstract: The 4875 A band of glyoxal has been photographed in absorption under high resolution and a rotational analysis carried out. The band is of type C fnd the principal mqlecular constants are:, vo = 20 507.57 cm-'. The A-rotational constants are smaller by a factor of -2 than the constants found earlier for trans glyoxal. The new results are consistent with the assignment of the band to an allowed 'B1-'Al (n*-n) transition of cis glyoxal. Temperature studies indicate that the cis isomer lies 1125 , 100 cm-' above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(22 citation statements)
references
References 2 publications
2
20
0
Order By: Relevance
“…t' p b . byl4 po ariza ion, d' can e given ( 1) where N 0 = Avagadro's number °" = polarizability of the molecule In addition to the distortion polarization, polar molecules also have orientation polarization, P, due to u the presence of a permanent dipole moment. 14 …”
mentioning
confidence: 99%
“…t' p b . byl4 po ariza ion, d' can e given ( 1) where N 0 = Avagadro's number °" = polarizability of the molecule In addition to the distortion polarization, polar molecules also have orientation polarization, P, due to u the presence of a permanent dipole moment. 14 …”
mentioning
confidence: 99%
“…This biradical would also be stabilized relative to CBD by relief of the repulsion between the carbonyl groups, which can be taken as about 3 kcal/mol, the difference between the heats of formation of cis-and trans-glyoxal (6,14). Taking this into account, an additional 10 kcal/mol of stabilization, persisting in the transition state, would still be needed to reach the 39.3 kcal/mol activation energy measured for CBD.…”
Section: Discussionmentioning
confidence: 99%
“…Looking at the absorption spectrum, we noticed that the rotational structure, while similar to that of glyoxal, showed about twice the number of sub-bands. Rotational analysis showed that the band was produced by a cis-isomer of the molecule (96). The molecule in this configuration has a dipole moment and the microwave spectrum was subsequently found.…”
Section: Asyrotmentioning
confidence: 95%